IMPLEMENTATION OF PROJECT-BASED LEARNING TO IMPROVE ORAL COMMUNICATION SKILLS OF 7TH GRADE STUDENTS IN NGANJUK - Rohmatin, Dewi Nur; Widodo, Catur Wahyu; Masfingatin, Titin (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2023)
The purpose of this study is to determine the effect of Project Based Learning implementation on improving students’ oral communication skills. The research method used was classroom action research with two learning cycles. The subjects in this study were students of class VII-C at one of the junior high school in Nganjuk. The data for this study were obtained from observation sheets and questionnaires on oral communication skills. This research uses Miles and Huberman’s qualitative data analysis with steps data reduction, data display, and conclusions drawing. The observation result showed that the average achievement indicator for oral communication skills in pre-cycle was 14.38%, cycle 1 was 30.72%, and cycle 2 was 47.71%. The results of the pre-cycle student response questionnaire was 19.28%, cycle 1 was 37.90% and cycle 2 was 50.37%. These show that there is an effect of implementing project based learning in the form of improving students’ oral communication skills.